Evaluasi Penggunaan Antihipertensi Dengan MetodeATC/DDDDiRSUD Dr.Moewardi Surakarta Periode Januari–Desember2022: Evaluation of the Use of Antihypertensives Using ATC/DDD Method In RSUD Dr. Moewardi Surakarta January – December 2022 Period - Yoga Pratama; Kusumaningtyas Siwi Artini; Tiara Ajeng Listyani (UIMA Press, 2023)
Hypertension is a condition where there is an increase in blood pressure that exceeds normal limits, namely systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. The use of appropriate antihypertensive drugs is one of the keys to successful treatment of hypertension. The purpose of this study was to determine the type of antihypertensive used in RSUD Dr. Moewardi Surakarta and its quantity calculated using the ATC/DDD method. This research is a descriptive study with retrospective data collection. Data on the use of antihypertensive drugs during 2022 will be taken from the pharmacy installation unit of RSUD Dr. Moewardi Surakarta and then will be processed to determine the type and quantity in DDD units. Data on antihypertensive use will be processed using Microsoft Excel, then compiled in tabular format. In addition to data on antihypertensive use, data will also be collected on outpatient visits every month during 2022 to calculate the quantity of antihypertensive use in DDD units/1000 outpatient visits. The results showed that the antihypertensive drugs used in RSUD Dr. Moewardi Surakarta per month in 2022 are amlodipine, hydrochlorothiazide, candesartan, captopril, and lisinopril and the quantity of antihypertensive drug use from January to December in 2022 with an average quantity of use from January to December is amlodipine 32,020.27 DDD/1000 KPRJ, hydrochlorothiazide 972.14 DDD/1000 KPRJ, candesartan 36,192.85 DDD/1000 KPRJ, captopril 544.68 DDD/1000 KPRJ, and lisinopril 1,524.08 DDD/1000 KPRJ. Drugs included in the 90% DU segment are amlodipine and candesartan.